Global burden prediction of gastric cancer during demographic transition from 2020 to 2040 - Chao Yan; Fei Shan; Xiangji Ying; Ziyu Li; Jing Ni (Chinese Medical Journal, 2023)
Abstract. Background:. Despite the decline in the incidence and mortality rates of gastric cancer (GC), the impact of demographic transition on the global burden of GC remains unclear. The current study aimed to estimate the global disease burden through 2040 by age, sex, and region. Methods:. GC data for incident cases and deaths by age group and sex were taken from The Global Cancer Observatory (GLOBOCAN) 2020. The incidence and mortality rates were predicted through 2040 by fitting a linear regression model over the most recent trend period with the Cancer Incidence in Five Continents (CI5) data. Results:. The global population will grow to 9.19 billion by 2040, accompanied by increasing population ageing. The incidence and mortality rates of GC will show a persistent decrease, with an annual percent change of –0.57% for males and –0.65% for females. East Asia and North America will have the highest and lowest age standardized rates, respectively. A slowdown in the growth of incident cases and deaths will be observed worldwide. The proportion of young and middle-aged individuals will decline, while the percentage of the elderly will increase, and the number of males will be almost twice the number of females. East Asia and high human development index (HDI) regions will be heavily burdened by GC. East Asia had 59.85% of the new cases and 56.23% of deaths in 2020; these will increase to 66.93% and 64.37% by 2040, respectively. The interaction between population growth, the change in ageing structure and the decline in incidence and mortality rates will lead to an increased burden of GC. Conclusions:. Ageing and population growth will offset the decline in the incidence and mortality rate of GC, resulting in a substantial increase in the number of new cases and deaths. The age structure will continue to change, especially in high HDI regions, requiring more targeted prevention strategies in the future.